2007
DOI: 10.1539/joh.49.9
|View full text |Cite
|
Sign up to set email alerts
|

HBV‐ and HCV‐ Infected Workers in the Japanese Workplace

Abstract: HBV-and HCV-Infected Workers in the Japanese Workplace, Rie NARAI, et al. Department o f E n v i r o n m e n t a l H e a l t h , U n i v e r s i t y o fOccupational and Environmental Health-Around three million Japanese are persistently infected with HBV or HCV. Though most of them work in various industries, little is known about the actual conditions in their workplaces. To clarify the workplace conditions of workers with hepatitis, three kinds of questionnaire surveys, answered by occupational health physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The estimated HCV prevalence was 1–1.9%. Published estimates come from a large number of blood donor (138, 143–149) and subgroup‐based studies throughout the country from 1991 to 2010 (140, 141, 145, 147, 150–184). A study of pregnant women in 1990–1994 found a prevalence of 0.3% in women <40, and 1.8% in women over 40, suggestive of the importance of historical risk factors (140).…”
Section: Resultsmentioning
confidence: 99%
“…The estimated HCV prevalence was 1–1.9%. Published estimates come from a large number of blood donor (138, 143–149) and subgroup‐based studies throughout the country from 1991 to 2010 (140, 141, 145, 147, 150–184). A study of pregnant women in 1990–1994 found a prevalence of 0.3% in women <40, and 1.8% in women over 40, suggestive of the importance of historical risk factors (140).…”
Section: Resultsmentioning
confidence: 99%
“…The literature concerning occupational health disparities and occupational health psychology seem to suggest that mental (e.g., burnout) or physical health disparities (e.g., CVD or asthma) may be attributed to working conditions and job characteristics such as ergonomic risk factors 20) ; exposures to vinyl chloride, silica, carbon fuel, wood dust, asbestos, mineral oils; or external ionizing radiation at work [21][22][23] ; amount of control or discretion at work [24][25][26][27][28][29][30] ; and skills and abilities required to perform tasks (e.g., regulating one's emotions and ways of expressing them to meet requirements at work 31) . Other contributing factors also include shift work and eating habits 32) , management and organizational structure 33) , safety and health climate 34) , nature of jobs that create conflict between work and family 35) , access to and utilization of quality health care 36) and organizational regulations or policies (e.g., sick leave policies or return to work policies).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, employers are often reluctant to hire people diagnosed with HIV, and may even dismiss a newly-diagnosed employee [3]. As a result, seropositive workers often avoid disclosing their infection status to employers in order to avoid prejudice and disadvantage [4] [5].…”
Section: Introductionmentioning
confidence: 99%